A Comparative Study on Music Curriculum Design in Universities based on AR technology: A Survey of 10 Undergraduate Colleges in Nanjing - Wang, Xin; Phokha, Pramote; Chiangthong, Nut (Journal of Ecohumanism, 2024)
Purpose: During the past few decades, there has been a huge increase in the usage of technological devices like mobile phones, which are now an indispensable part of our everyday lives. AR-based applications for smartphones and tablets have proven to be a game-changer in a number of fields, most notably education. Currently, Nanjing’s college music programmes are undergoing a fast development. Universities are currently experiencing innovation and a reform of their teaching methods in the field of music education. Improving music education in higher education institutions has emerged as a crucial concern for the music Students in Nanjing’s undergraduate institutions. Method: An analysis of how AR technology has affected the evolution of music curricula in undergraduate institutions in Nanjing through comparisons. Pre- and post-tests were used to evaluate the cultural understanding and motivation for the study of music of both groups. An Overview of Ten Nanjing Bachelor Colleges. Through the use of augmented reality technology, the experimental team introduced undergraduates’ students to a range of cultural contexts, practices, and norms. Results: The results show that as compared to the control group, the experimental group, which received AR-based training, had noticeably greater levels of intercultural competency and motivation for music learning. Conclusion: Quantitative data analysis revealed that AR-based training increased undergrad participants’ involvement, motivation, and understanding of culture. This study provides insights into prospective patterns and paths that AR technology could take in learning, giving readers a preview of future advances. This comprehensive viewpoint provides teachers, scholars, and professionals with significant insights into the instructional implications, technological characteristics, and practical issues of AR. Increasing the development of music education in institutions of higher learning can play an obvious role in helping to grow the influence.